2022
DOI: 10.1001/jamanetworkopen.2022.39796
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pediatric Buccal Epigenetic Age Acceleration With Adverse Neonatal Brain Growth and Neurodevelopmental Outcomes Among Children Born Very Preterm With a Neonatal Infection

Abstract: ImportanceVery preterm neonates (24-32 weeks’ gestation) remain at a higher risk of morbidity and neurodevelopmental adversity throughout their lifespan. Because the extent of prematurity alone does not fully explain the risk of adverse neonatal brain growth or neurodevelopmental outcomes, there is a need for neonatal biomarkers to help estimate these risks in this population.ObjectivesTo characterize the pediatric buccal epigenetic (PedBE) clock—a recently developed tool to measure biological aging—among very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Resilience and coping mechanisms aid in controlling emotions and changing the interaction between the person and the stressor, which reduces the stressor's physiologic effects ( 84 86 ). Adverse psychosocial factors in early childhood may also contribute to higher susceptibility to maladaptive stress responses that may manifest in adulthood since it can be imprinted on the developing brain ( 87 , 88 ). For example, individuals who experience chronic stress as children often have a higher prevalence of systemic illnesses as adults, including heart disease ( 89 ) and autoimmune diseases ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resilience and coping mechanisms aid in controlling emotions and changing the interaction between the person and the stressor, which reduces the stressor's physiologic effects ( 84 86 ). Adverse psychosocial factors in early childhood may also contribute to higher susceptibility to maladaptive stress responses that may manifest in adulthood since it can be imprinted on the developing brain ( 87 , 88 ). For example, individuals who experience chronic stress as children often have a higher prevalence of systemic illnesses as adults, including heart disease ( 89 ) and autoimmune diseases ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is notable, as epigenetic aging is a potential indicator of negative health and developmental trajectories for offspring. 48 Epigenetic aging in children has been associated with alterations in brain volumes, cortical thickness, cortical surface areas and abnormalities in neuronal microstructure in a range of brain regions; as well as a range of other offspring developmental and behavioral outcomes. 49 In data from ALSPAC, cumulative and individual ACE exposure of the offspring themselves during childhood (aged 0-14 years), including emotional and physical abuse, were linked to epigenetic age acceleration through 17 years of age, with stronger effect estimates in females.…”
Section: Discussionmentioning
confidence: 99%
“…This is notable, as epigenetic aging is a potential indicator of negative health and developmental trajectories for offspring. 48 Epigenetic aging in children has been associated with alterations in brain volumes, cortical thickness, cortical surface areas and abnormalities in neuronal microstructure in a range of brain regions; as well as a range of other offspring developmental and behavioral outcomes. 49…”
Section: Discussionmentioning
confidence: 99%
“…Further, the direction of the effects of epigenetic age acceleration suggested that increased levels of positive parenting are related to improved health. Research on the relation between epigenetic age acceleration and prospective child health is limited in pediatric samples; however, emerging science suggests that higher levels of epigenetic age acceleration associates with poor health outcomes (e.g., internalizing disorders, Dammering et al, 2021; reduced neonatal brain growth, Gomaa et al, 2022). Our findings suggest that interventions targeting parenting practices may promote resilience in children exposed to adversity.…”
Section: Discussionmentioning
confidence: 99%